Attitudes towards (joining) the European Union in Croatia: An Overview - Landripet, Ivan (2006)
Attitudes of general population towards the European Union, mainly considered in terms of euro-skepticism and euro-optimism, are crucial in bilateral relations with the EU, whether a country is an EU member or aspires to become one. In case of the later, a milestone in each county's accession to full EU membership is referendum on the membership, which makes "euro-sentiments" of citizens one of the key political and social issues in the accession process. This presentation will offer an overview of recent research efforts on public views of (joining) the EU in Croatia and the main factors that determine them. In addition, I will present the relevant public opinion dynamics in some of the "new" EU member-states in order to compare the experiences, as well as to indicate possible predicaments of the final stages of Croatia's EU integration process. The aim is also to provide an outline of intervention strategies that the government should employ to reduce the level of euro-skeptic and anti-European sentiments among the citizens.